Frontiers in Optics / Laser Science 2018
DOI: 10.1364/ls.2018.lm1b.2
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-Limited Discrimination between Laser Light and Noise

Abstract: To determine the fundamental sensitivity limit of an optical receiver one must have a complete quantum mechanical description of the incoming signals, even if those signals are from "classical" sources of light, i.e., ones whose photo-detection statistics with conventional receivers can be explained correctly using the shot-noise theory. In this work, we calculate the fundamental (quantum) limit for discriminating between two types of classical states in the low photon number regime: a coherent state, a pure-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The experiments showed that the GK receiver closely approaches the Helstrom bound, while the Kennedy receiver was shown to be sub-optimal. Our work here shows both experimentally and analytically that the situation is reversed for multi-copy discrimination: the Kennedy receiver exactly attains the QCB, as expected [13,22], whereas the GK receiver is decidedly not optimal by a provable factor.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…The experiments showed that the GK receiver closely approaches the Helstrom bound, while the Kennedy receiver was shown to be sub-optimal. Our work here shows both experimentally and analytically that the situation is reversed for multi-copy discrimination: the Kennedy receiver exactly attains the QCB, as expected [13,22], whereas the GK receiver is decidedly not optimal by a provable factor.…”
mentioning
confidence: 63%
“…We observe that ξ QCB > ξ GK > ξ Helstrom , with the quantum Chernoff bound (achieved by the Kennedy receiver) exceeding both ξ GK and ξ Helstrom by at least a factor of two. We also note that coherent homodyne detection, another common classical receiver, achieves a discrimination error exponent equal to that for the ideal Helstrom receiver, as shown in [13].…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…As a proof-of-concept, we investigate a NN-based method for tracking phase and amplitude channel noise, that uses only the data collected during the state discrimination measurement. This NN-based method can be easily extended to perform higher dimensional parameter estimation for tracking additional sources of noise in the channel such as thermal noise [33,34] or phase diffusion [35][36][37]. In this section, we describe (A) the measurement strategy of the non-Gaussian receiver for coherent state discrimination; (B) how the data from the measurement is used by the NN; and (C) the NN estimator, which can be used for estimation of channel noise from multiple sources.…”
Section: Receiver and Estimation Strategymentioning
confidence: 99%
“…In more realistic situations there may be multiple sources of noise present in the communication channel, such as thermal noise [33,34], phase diffusion [35][36][37], phase noise, and amplitude noise. In such situations the non-Gaussian receiver must perform efficient highdimensional parameter estimation and tracking in order to maintain the expected sub-QNL performance.…”
Section: Introductionmentioning
confidence: 99%